Screening of preliminary phytochemicals of Hamelia patens plant - JAFRABANO,; SWAPNA SANTRA,; EKTA MENGHANI, (International Journal of Pharma and Bio Sciences, 2017)
Hamelia patens belong to family rubiaceae and this study for discover the presence of phytochemicals in thisplant. (leaf, stem, flower and root). Various solvents extracts such as methanol, benzene, dichloromethane, ethyl acetate and hexane have been used for the qualitatively analysis.In qualitative analysis the phytochemical compounds such as flavonoids, alkaloids, Phenolic, glycosides, carbohydrate, protein, sterol and acidic compound were screened with the six extracts. The methanolic extract showed positive results for the 10 phytochemical tests. The benzene extract demonstrates positive results for the 9 tests. In the chloroform and dichloromethane extractsconfirmed positive results for the 9 tests and in the ethyl acetate extractillustrated positive results for 9 tests and in the ethyl acetate extract 8 phytochemical tests were positive. In qualitative analysis important secondary metabolites such as alkaloids, flavonoids, Phenolic, were tested in all the extracts. The methanol extract revealed highest amount of phytochemicals when compared with other extracts.